Correction to: Changes in feeding habits promoted the differentiation of the composition and function of gut microbiotas between domestic dogs (Canis lupus familiaris) and gray wolves (Canis lupus) - Tianshu Lyu; Guangshuai Liu; Huanxin Zhang; Lidong Wang; Shengyang Zhou; Huashan Dou; Bo Pang; Weilai Sha; Honghai Zhang (AMB Express, 2021)
An amendment to this paper has been published and can be accessed via the original article.